Financial Challenges as One of the Barriers to Achieving Educational Goals - Fauzan Huda Perdana; Melinda Khaila Nurfadilla; Muhammad Wahyu Daffa Dien; Siti Sopa Lismaya; Syifa Nurjamilah Fatwa Fadilah (Penerbit Hellow Pustaka, 2024)
This article discusses financial challenges as one of the main obstacles to achieving educational goals. In the context of low levels of education, it was revealed that financial constraints were the main cause. This research aims to identify the impact of finance on access and quality of education and explore possible solutions to overcome this problem. The research method used is analysis of related data from previous research studies. The findings show that families with financial constraints face difficulties in providing adequate educational facilities for their children, which directly affects their educational outcomes. This article also discusses the impact of finance on educational inequality and access to equal educational opportunities. In conclusion, this article formulates the importance of government policies and assistance that support fair and equitable access to education, by providing financial assistance to families in need. In addition, collaborative approaches between government, schools and communities need to be strengthened to overcome these financial challenges and create an inclusive and equitable educational environment.